Genetic Diversity Analysis of Mulberry Silkworm (Bombyx Mori L.) Hybrids and Breeds in Azerbaijan Using RAPD Markers - Mammadov Ayaz; Aghayeva Saltanat; Bakırov Guduret; Gulubeyova Mahpuba; Ismayılova Gular (BIO Web of Conferences)
In order to study the genetic diversity of silkworms (Bombyx mori L.) breeding in Azerbaijan, the following breeds and hybrids were analyzed: SHZEM 4 x GE 143, Chingiz x Yagub, Yagub x Chingiz, GE 143, Yagub, SHZEM 4 belted, Chingiz, GE 143 x SHZEM 4 using RAPD molecular markers. For this purpose, silkworm larvae were taken for DNA extraction and nuclear genome DNA was isolated from various parts of the silkworm (silk gland, epidermis, etc.). Four RAPD primers (BGN 04, BGL 02, BGY 06, BGA 02) were used in the study, resulting in 200-1200 bp 34 dots representing fragments. The average number of amplicons for each primer was 6-11, and 82-100% of the amplicons were polymorphic. The study found that RAPD markers do not fully reflect the similarity between the local breed and hybrids.